1993
DOI: 10.2172/10108235
|View full text |Cite
|
Sign up to set email alerts
|

Composting of soils/sediments and sludges containing toxic organics including high energy explosives. Final report

Abstract: Cunently available technology isnotadequate toassess environmental contamination at Department of Energy ('_.")E)sites, take permanentremedial action, and eliminate or minimize theenvironmental impact offuture operations. Technical resources toaddress these shortcomings exist within theDOE community andthe private sector, buttheinvolvement oftheprivate sector inattaining permanent andcost-effective solutions hasbeenlimited. During 1990, on behalf ofDOE's Office ofTechnology Development, ArgonneNational Laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
(1 reference statement)
1
3
0
Order By: Relevance
“…MBC showed high percentage degradation of explosive which might be attributed to the synergistic effect (HGT) between the catabolic enzymes in the eight bacteria isolates. These findings are similar to the result obtained by Duniya et al, 45 whose research reported biodegradation rates at 97% by MBC reported. 143 Isolated bacteria species at the study site with potential for biodegradation of explosives are bacillus sp; Escherichia coli, Enterobacter sp, Klebsiella nitroreductases, Genes required for degradation of xenobiotic may be recruited by various horizontal transfer mechanisms 93 so that lateral gene transfer could be involved in the broad distribution of nitroreductases in prokaryotic organisms.…”
Section: Resultssupporting
confidence: 92%
“…MBC showed high percentage degradation of explosive which might be attributed to the synergistic effect (HGT) between the catabolic enzymes in the eight bacteria isolates. These findings are similar to the result obtained by Duniya et al, 45 whose research reported biodegradation rates at 97% by MBC reported. 143 Isolated bacteria species at the study site with potential for biodegradation of explosives are bacillus sp; Escherichia coli, Enterobacter sp, Klebsiella nitroreductases, Genes required for degradation of xenobiotic may be recruited by various horizontal transfer mechanisms 93 so that lateral gene transfer could be involved in the broad distribution of nitroreductases in prokaryotic organisms.…”
Section: Resultssupporting
confidence: 92%
“…Composting has been used to treat a wide variety of sludges and soils contaminated with organonitro explosives, including PETN. [Doyle 1993] Fungi are thought to play a vital role in the composting treatment process. In isotopically labeled laboratory-scale compost tests, PETN was mineralized to some extent although highly polar 14 C-compounds were initially found in the composts.…”
Section: I) Biological Activitymentioning
confidence: 99%
“…In a study by Doyle and Kitchens (1993) soil from the Pantex Plant was used to evaluate composting as a remediation method for RDX, HMX, triaminotrinitrobenzene (TATB), and pentaerythritoltetranitrate (PETN) contamination. In laboratory tests uncontaminated soils samples were spiked with 220 pg/g RDX, 220 pg/g HMX, 400 pg/g PETN, and 2700 pg/g TATB.…”
Section: Soil Cornpostingmentioning
confidence: 99%
“…Numerous laboratory and field tests have achieved degradation efficiencies greater then 90% for RDX and HMX using a variety of composting materials (Doyle, et al 1986;Doyle and Kitchens. 1993;Griest, et al 1990;Isbister, et al 1982;Williams, et al 1992).…”
mentioning
confidence: 99%